Planejamento bim 4d e simulação construtiva em silos metálicos planos - Dias, Raul Pinheiro (2021)
Brazilian agribusiness consolidates itself year after year as the most important sector of the national economy, which makes its aspects objects of interest and study by the government, private companies, cooperatives and researchers, being the storage of grain a fundamental part of this process, mainly due to the deficit between storage capacity and production. One of the main ways to store grains is by flat-bottomed metal silos, which is an specific type of agricultural construction, with multidisciplinary characteristic, as integrates earthwork, civil and metalic services, mechanical assembly, and electrical installations, which must be correctly coordinated. To do so, the BIM methodology and its dimensions provide subsidy for improving the life-cycle project, from conception to maintenance. Therefore, in this research it was used the forth BIM dimension, known as 4D BIM, as a proposal regarded to the process innovation, which embraces the planning phase to the construction conception of a flat-bottomed metal silos battery, through creation of a three dimensional model, listing of tasks, schedule elaboration and development of a four dimensional model, in Autodesk Navisworks Manage 2019, which used Timeliner and Clash Detective to create the opportunity for analysing and simulating execution, what made the spatial temporal conflicts anticipation possible, and detecting geometrical interferences, respectively. As result, twenty two important clashes, identified in the model, were treated individually, which reflected in a 30% reduction in the deadline of executive schedule. Lastly, the analysis and bibliographic researches carried out served as a basis to produce a checklist of main items to be considered and checked in works of flat-bottomed metal silos , that assists the decision-making process for clients and contractors, when in grain storage facilities projects all over the country.